Lupus Panniculitis as a Complication of Herpes Zoster - Genç, Volkan; Genç, Aysun; Karaca, Ahmet Serdar; Çipe, Gökhan; Nergiz, Elif; Başçeken, Salim İlksen; Turgay, Murat (Fırat University, 2011)
A 55-year-old woman with a 7 year history of systemic lupus erythematosus was consulted to our surgical clinic from immunology department due to exhausting left inguinal pain. She was diagnosed with herpes zoster but her complaints increased despite of the treatment of herpes zoster. Magnetic resonance imaging showed the fluid collection, cutaneous and subcutaneous oedema association with panniculitis only in the herpes zoster area. We think that panniculitis in our patient is triggered by herpes zoster infection because of same location of these two diseases. It is first reported entity which shown correlation between viral infections and lupus panniculitis.

Yedi yıllık sistemik lupus eritematozus hikayesi olan 55 yaşındaki kadın hasta sol inguinal ağrı nedeni ile immunoloji bölümünden cerrahi kliniğimize konsulte edildi. Hasta herpes zoster tanısı almıştı fakat tedaviye rağmen şikayetleri artmıştı. Manyetik rezonans görüntüleme herpes zoster bölgesinde pannikülitle uyumlu olarak sıvı koleksiyonu, cilt ve cilt altı dokuda ödemi gösterdi. Biz bu iki hastalığın aynı lokalizasyonda oluşması nedeni ile pannikülitin herpes zoster infeksiyonun tetiklemesi sonucu oluştuğunu düşünmekteyiz. Bu olgu viral infeksiyonlar ile lupus panniküliti arasındaki ilişkisinin gösterildiği ilk rapordur.
Herpes Zoster'in Komplikasyonu Sonucu Oluşan Lupus Panniküliti